استخدام نموذج الأداء المتوازن في تقويم أداء المستشفيات "دراسة تطبيقية في مستشفى الباسل بطرطوس" - الغصين, راغب; تامر, وسام جبّار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى تقويم الأداء في مستشفى الباسل بطرطوس باستخدام نموذج الأداء المتوازن, ولتحقيق أهداف البحث تمّ تصميم استبانة, وتطبيقها على عينة من العاملين في المستشفى, وانتهى البحث إلى النتائج التالية: 1- يعد نموذج الأداء المتوازن الأداة الأفضل والأكثر موضوعية لتقويم أداء مستشفى الباسل بطرطوس, لأنه يتيح التعرف على مايتم تحقيقه من نتائج في كل قسم أو دائرة في المستشفى. 2- عدم وجود تطبيق متكامل لنموذج الأداء المتوازن في المستشفى بسبب ضعف الخبرات الفنية المؤهلة اللازمة لتدريب العاملين عليه. 3- وجود فروق ذات دلالة إحصائية بين متوسطات استجابات أفراد العينة تبعاً لمتغيرات المؤهل العلمي وسنوات الخبرة. 4- عدم وجود فروق ذات دلالة إحصائية بين متوسطات استجابات أفراد العينة تبعاً لمتغير طبيعة العمل. This research aims to evaluate the performance in Al-Basel Hospital in Tartous by using the Balanced Performance Model, and to achieve the research objectives, a questionnaire was devised and applied on a sample of the workers in the hospital. The research concluded the following results: 1- The Balanced Performance Model is considered the best and most objective to evaluate the performance in Al-Basel Hospital in Tartous, because it helps to get an idea about what is being achieved in every department or administration in the hospital. 2- There is no complementary application for the balanced performance model in the hospital due to the lack of the trained technical expertise that are necessary to train the trainees. 3- There are statistically significant differences between the means of sample subjects' responses according to the variables of the scientific degree and years of experience. 4- There are no statistically significant differences between the means of sample subjects' responses according to the variables of nature of work.